Landslide hazard evaluation in and around the Ilam Hydropower Project, Eastern Nepal Himalaya - Chamlagain, Deepak; Dangol, Vishnu (Journal of Nepal Geological Society, 2002)
The paper describes the results of the engineering geological and landslide hazard evaluation studies carried out in and around the Ilam Hydropower Project, eastern Nepal. Various types of mass wasting phenomena such as gully erosion, bank undercutting, and landslides are observed along the Mai Khola, Puwa Khola and road corridors. Gully erosion and bank undercutting are common on the slopes adjacent to streams and gullies. Most of the landslides are located on the slopes of 25° to 40° whereas large rock falls are found on the slopes, which are steeper than 40°. South-facing dip slopes contain large landslides while north-facing slopes seem to be relatively stable. The population of translational slide is dominant in the study area and is found mostly on soil having a depth of 3-6 m. Most of the rock falls are confined in schistose gneiss and highly fractured quartzite. Generally, three sets of joints govern the failure pattern of rockslides. The main triggering factors for mass movement of the area are high intensity of rainfall, rock discontinuities, steep topography, poor vegetation and river scouring. Land use pattern of the area has also equally contributed to initiate the mass movements in the area. The high hazard zones for rock slopes were confined to the steep dip slopes with highly fractured rocks whereas soil slope hazard is confined to fault zones and south facing slope. The soil slope was found to be more hazardous than the rock slope. The main causative factors for the landslide hazard in the study area are steep slope, rock discontinuity, land use pattern, soil depth and rainfall.